2008
DOI: 10.1182/blood-2007-12-126979
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive usage of monoclonal immunoglobulin λ light chain germline in POEMS syndrome

Abstract: POEMS syndrome is a rare plasma cell disorder characterized by peripheral neuropathy, monoclonal gammopathy, and high levels of serum vascular endothelial growth factor, the pathogenesis of which remains unclear. A unique feature of this syndrome is that the proliferating monoclonal plasma cells are essentially -restricted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 24 publications
3
39
0
1
Order By: Relevance
“…Our result is consistent with the finding from the previous three studies [4][5][6]. Combining results from all four studies, there are 57 cases to demonstrate that IGLV gene was strictly derived from either IGLV 1-40 or IGLV 1-44 gene in POEMS syndrome.…”
Section: Discussionsupporting
confidence: 96%
See 2 more Smart Citations
“…Our result is consistent with the finding from the previous three studies [4][5][6]. Combining results from all four studies, there are 57 cases to demonstrate that IGLV gene was strictly derived from either IGLV 1-40 or IGLV 1-44 gene in POEMS syndrome.…”
Section: Discussionsupporting
confidence: 96%
“…For example, Soubrier et al first reported that two POEMS patients had M protein derived from the IGLV 1-40 gene [4]. Abe et al found that IGLV genes were restricted to two genes in 11 patients-nine patients had IGLV 1-44 and two patients had IGLV 1-40 [5]. Dispenzieri et al also reported that IGLV genes were either IGLV 1-40 or IGLV 1-44 in 14 patients [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…1,2,27 Mutations are clearly relevant for destabilization of the LC molecule, a critical aspect related to amyloidogenicity. 1,2,27 In this view, it will be of interest to compare amyloid-forming IGVL1-44 LC with LC from POEMS syndrome, 28 a rare nonamyloid plasma cell disorder that is characterized by significant overuse of IGVL1-44 sequences, 29 to identify possible disease-related structural features. Unlike IGVL3-1 and IGVL6-57, IGVL1-44 is then clearly not exclusively associated with amyloidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 -IMWG criteria for PEOMS syndrome Elevated VEGF levels in patients with POEMS syndrome is important as it is implicated in the pathogenesis of the syndrome itself 4 but we hadn't estimated its level in our patient because the development of polyneuropathy in POEMS syndrome is thought to be VEGF related. The presence of monoclonal plasma cell disorder is almost always present in POEMS and predominantly lambda type of light chain as seen in our patient 5 . It is known that the M Band on protein electrophoresis is usually seen in the Gamma region but patient showed the M band spike in the Beta-1 regions which is less common.…”
Section: Figure 1 -Osteosclerotic Changes Of Ls Spinementioning
confidence: 65%